2011
DOI: 10.1080/02755947.2011.561163
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Diploid and Triploid Rainbow Trout Stocked in Idaho Alpine Lakes

Abstract: Increased growth, improved survival, and genetic protection of wild stocks have been suggested as benefits of stocking triploid (i.e., sterile) salmonids for recreational fisheries. We examined the return rates and growth of mixed‐sex diploid (2N), mixed‐sex triploid (3N), and all‐female triploid (AF3N) rainbow trout Oncorhynchus mykiss across 28 alpine lakes. Equal numbers of each treatment group were stocked in 2001 and 2003 and sampled 3–4 years later. During 2004 and 2005, a total of 75 2N and 36 3N marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Stocking triploids is an alternative to effectively avoid interbreeding of hatchery fish and wild fishes, thereby minimizing the impacts of wild stocks in the long‐term while providing fishing opportunities (Koenig et al. , Lorenzen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Stocking triploids is an alternative to effectively avoid interbreeding of hatchery fish and wild fishes, thereby minimizing the impacts of wild stocks in the long‐term while providing fishing opportunities (Koenig et al. , Lorenzen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; High & Meyer ; Koenig et al . ; Koenig & Meyer ). Unfortunately, none of these studies examined the diet of the stocked triploids, which would indicate whether they might displace wild fish.…”
Section: Impacts Of Triploidy On Phenotypic Characteristics Relevant mentioning
confidence: 99%
“…When mixed‐sex triploid Rainbow Trout were stocked into recreational fisheries in Idaho alpine lakes, their survival was less than that of diploids (Koenig et al. ). Koenig and Meyer () indicated that although survival and return to anglers were greater for stocked diploid all‐female Rainbow Trout than for concurrently stocked triploids, the triploids still represented a viable option for fishery managers, especially in application to waters with high‐quality habitat.…”
mentioning
confidence: 99%